Knowledge of Mpox, Media Exposure, and Clinical Experience: - Aime Fidele Ndayiragije Mvuyekure; Simon Pierre Ndayishimye Mvuyekure; Daniel Muhayimana; Jean Claude Tuyishime; Anifa Munderere (Pan-African Journal of Health and Environmental Science)
Background: This study aimed to determine the predictors of nursing students’ preparedness for disease outbreaks and the relationships between knowledge of Mpox, media exposure, and clinical experience, as moderated by demographic variables. One hundred respondents were selected using stratified random sampling from four academic levels at the University of Gitwe.